Redox-Triggered Buoyancy and Size Modulation of a Dynamic Covalent Gel - Das, Gobinda; Nagaraja, Sharadhi; Sridurai, Vimala; Shinde, Digambar B; Addicoat, Matthew; Prakasam, Thirumurugan; Gándara, Felipe; Ravaux, Florent; Sharma, Sudhir Kumar; Nair, Geetha G; Lai, Zhiping; Jagannathan, Ramesh; et al. (Chemistry of materials, 2019)
The development of stimuli-responsive materials capable of transducing external stimuli into mechanical and physical changes has always been an intriguing challenge and an inspiration for scientists. Several stimuli-responsive gels have been developed and applied to biomimetic actuators or artificial muscles. Redox-active actuators in which the mechanical motion is driven chemically or electrochemically have attracted much interest, and their actuation mechanism is based on the change in electrostatic repulsion and the loss or gain of counterions to balance newly formed charges. Actuation can also be promoted by changing the hydration state of the material, leading to the release/adsorption of water molecules from the network, inducing a direct shrinking/swelling of the material, respectively. A cationic crystalline dynamic covalent gel was obtained via the formation of imine bonds between 2,6-diformyl pyridine and triamino guanidinium chloride. The gel exhibits a reversible contraction/expansion behavior in response to base (oxidation, −H+, −e–) and acid (reduction +H+, +e–), respectively. The oxidation induces a color change and contraction of the gel with a concomitant increase in its strength. As synthesized, the cationic gel is denser than water and sinks when placed in water. Upon oxidation, the radical cationic gel expels water molecules, rendering it less dense than water and the gel is propelled to the surface without any loss of its structural integrity. These results demonstrate that a careful choice of amine and aldehyde linkers can give rise to imine-linked materials capable of tolerating and resisting extreme acidic and basic conditions while performing work.